Recent Advances in the Evaluation of Serological Assays for the Diagnosis of SARS-CoV-2 Infection and COVID-19 - Chiereghin, Angela; Zagari, Rocco Maurizio; Galli, Silvia; Moroni, Alessandra; Gabrielli, Liliana; Venturoli, Simona; Bon, Isabella; Rossini, Giada; Saracino, Ilaria Maria; Pavoni, Matteo; Lafratta, Silvia; Deni, Alessandro; et al. (Frontiers in Public Health, 2021)
Few data on the diagnostic performance of serological tests for SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) infection are currently available. We evaluated sensitivity and specificity of five different widely used commercial serological assays for the detection of SARS-CoV-2–specific IgG, IgM and IgA antibodies using reverse transcriptase-PCR assay in nasopharyngeal swab as reference standard test.Methods: A total of 337 plasma samples collected in the period April-June 2020 from SARS-CoV-2 RT-PCR positive (n=207) and negative (n=130) subjects were investigated by one point-of-care lateral flow immunochromatographic assay (LFIA IgG and IgM, Technogenetics) and four fully automated assays: two chemiluminescence immunoassays (CLIA-iFlash IgG and IgM, Shenzhen YHLO Biotech and CLIA-LIAISON® XL IgG, DiaSorin), one electrochemiluminescence immunoassay (ECLIA-Elecsys® total predominant IgG, Roche) and one enzyme-linked immunosorbent assay (ELISA IgA, Euroimmune). Results: The overall sensitivity of all IgG serological assays was >80% and the specificity was >97%. The sensitivity of IgG assays was lower within 2 weeks from the onset of symptoms ranging from 70.8% to 80%. The LFIA and CLIA-iFlash IgM showed an overall low sensitivity of 47.6% and 54.6%, while the specificity was 98.5% and 96.2%, respectively. The ELISA IgA yielded a sensitivity of 84.3% and specificity of 81.7%. However, the ELISA IgA result was indeterminate in 11.7% of cases. Conclusions: IgG serological assays seem to be a reliable tool for the diagnosis of SARS-CoV-2 infection. IgM assays seem to have a low sensitivity and IgA assay is limited by a substantial rate of indeterminate results.